Multi-view large population gait dataset and its performance evaluation for cross-view gait recognition - Takemura, Noriko; Makihara, Yasushi; Muramatsu, Daigo; Echigo, Tomio; Yagi, Yasushi (IPSJ transactions on computer vision and applications, 2018)
This paper describes the world’s largest gait database with wide view variation, the “OU-ISIR gait database, multi-view large population dataset (OU-MVLP)”, and its application to a statistically reliable performance evaluation of vision-based cross-view gait recognition. Specifically, we construct a gait dataset that includes 10,307 subjects (5114 males and 5193 females) from 14 view angles ranging 0° −90°, 180° −270°. In addition, we evaluate various approaches to gait recognition which are robust against view angles. By using our dataset, we can fully exploit a state-of-the-art method requiring a large number of training samples, e.g., CNN-based cross-view gait recognition method, and we validate effectiveness of such a family of the methods.